2017
DOI: 10.1016/j.ejso.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of treatment of advanced dermatofibrosarcoma protuberans (DFSP) with imatinib mesylate – The impact of fibrosarcomatous transformation

Abstract: Our results indicate the long-term activity of imatinib in therapy of inoperable and/or metastatic cases of DFSP, including FS-DFSP. Some DFSP patients initially evaluated as unresectable/metastatic or necessitating mutilating surgery turned resectable after imatinib therapy and this rational approach leading to complete remission maybe potentially curative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 41 publications
(19 reference statements)
0
48
0
2
Order By: Relevance
“…To date, there has been no clinical study directly comparing various imatinib doses in the treatment of DFSP. A real‐world study of 31 patients treated with imatinib for advanced DFSP showed a progression‐free 5‐year survival rate of 58 % and an overall 5‐year survival rate of 64 % (median follow‐up of 5.3 years) . Shorter survival times on imatinib were associated with the histological subtype of fibrosarcomatous DFSP (DFSP‐FS) as well as with the presence of metastases .…”
Section: Treatmentmentioning
confidence: 99%
“…To date, there has been no clinical study directly comparing various imatinib doses in the treatment of DFSP. A real‐world study of 31 patients treated with imatinib for advanced DFSP showed a progression‐free 5‐year survival rate of 58 % and an overall 5‐year survival rate of 64 % (median follow‐up of 5.3 years) . Shorter survival times on imatinib were associated with the histological subtype of fibrosarcomatous DFSP (DFSP‐FS) as well as with the presence of metastases .…”
Section: Treatmentmentioning
confidence: 99%
“…In addition, radiotherapy may be useful in patients with positive surgical margins, to reduce the risk of local recurrence, and in cases where surgery would result in major cosmetic defects. Several published reports have indicated that imatinib mesylate can be considered as an optimal therapeutic choice in patients with metastatic or locally advanced DFSP . Tsai et al reported 13 pediatric DFSP patients who received a wide local excision (25 mm‐30 mm), and neither recurrence nor metastasis was observed from 20 months to 19 years after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of imatinib (400 vs 800 mg) did not have a significant differential treatment effect 67. Furthermore, the presence of a fibrosarcomatous component in DFSP was correlated with worse imatinib activity in terms of PFS and OS 68…”
Section: Part 1 Developed Genomic-guided Precision Therapy For Stsmentioning
confidence: 96%